Phytochemical Profiling and Antibacterial Efficacy of Azadirachta indica Against Antimicrobial-Resistant Escherichia coli, Pseudomonas aeruginosa, and Salmonella typhi Isolated from Dental Plaque - Aisha Marafa Mahmud; AbdulAzeez Mumsiri Abaka; Zainab Abubakar (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2026)
The global rise of antimicrobial resistance (AMR) underscores an urgent need for alternative therapeutic strategies. Dental plaque has been identified as a key reservoir for multidrug-resistant bacteria, presenting a significant clinical challenge. Aqueous and methanolic extracts were prepared using cold maceration. Qualitative phytochemical screening identified the presence of alkaloids, flavonoids, tannins, saponins, cardiac glycosides, and steroids. Antibacterial activity was evaluated through agar well diffusion (to determine zones of inhibition), broth microdilution (for Minimum Inhibitory Concentration/MIC and Minimum Bactericidal Concentration/MBC), and biofilm inhibition assays. Both extracts exhibited concentration-dependent antibacterial effects. The aqueous extract demonstrated the highest potency, showing the largest mean inhibition zone against Staphylococcus aureus (26.07 ± 0.61 mm at 200 mg/mL) and the lowest MIC values (1.562 mg/mL) against both S. aureus and E. coli. The methanolic extract was most effective against E. coli (MIC = 3.125 mg/mL). MBC assays confirmed the extracts' bactericidal action, eliminating S. aureus at 75 mg/mL and Gram-negative pathogens at 100 mg/mL. Biofilm formation was also significantly reduced at sub-inhibitory concentrations. The superior efficacy of the aqueous extract validates traditional aqueous-based preparations and highlights the critical role of solvent polarity in extracting bioactive compounds. The broad-spectrum antibacterial activity correlates directly with the rich profile of secondary metabolites, particularly polyphenols and alkaloids, providing a scientific basis for neem's historical medicinal use. By demonstrating significant activity against resistant, plaque-derived pathogens, this research addresses a notable gap in the literature and positions A. indica as a promising source of antibacterial agents. The findings advocate for subsequent bioassay-guided fractionation of the aqueous extract to isolate and characterize the specific compounds responsible for its activity, facilitating the development of novel adjunctive treatments for AMR.